When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments. Issue 7 (16th January 2023) - Van Sundert, Kevin; Leuzinger, Sebastian; Bader, Martin K.‐F.; Chang, Scott X.; De Kauwe, Martin G.; Dukes, Jeffrey S.; Langley, J. Adam; Ma, Zilong; Mariën, Bertold; Reynaert, Simon; Ru, Jingyi; Song, Jian; et al.
Abstract: Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO2, temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57, 089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO2, warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253, opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub. Abstract : A wide range of experiments have been conducted that manipulate CO2, temperature, and nutrient and water availability in terrestrial ecosystems. Syntheses of results across such experiments provide a general sense of ecosystem responses to global change. We report on an effort to collect and curate 57, 089 treatment responses across 3644 manipulation experiments at 1145 sites. In the resulting "MESI" database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data, including, unique to our database, measured soil properties. MESI is freely accessible at doi.org/10.5281/zenodo.7153253 . We welcome contributions to the database on GitHub.